Changing terrain: evidence of climate change impacts and adaptive responses of Dagbani Indigenous Communities, northern Ghana - Attoh, Emmanuel M. N. A. N.; Afriyie, R.; Kranjac-Berisavljevic, G.; Bessah, E.; Ludwig, F. (Routledge, 2024)
This chapter presents observations of changes attributed to climate change and adaptation actions taken by Indigenous communities in Kumbungu – Northern Ghana. Using focus group discussions and simple random and convenience quota sampling techniques, 125 households and 175 individuals were interviewed. Results showed an increase in rainfall variability, frequency of heavy rainfall events, hot/warm days and average temperature; shortened growing season; increased frequency of crop pests and wildfire, and livestock mortality, all of which significantly affect households. To respond to climate impacts, respondents applied chemical fertilizers, changed crop varieties, planted trees, used sandbags against floods, used weather and seasonal forecast information, and engaged in off-farm activities. A key barrier to adaptation is the lack of financial resources. We recommend: (1) micro-credit schemes to support Indigenous people’s adaptation choices; (2) the provision of accurate weather and seasonal climate forecast information for actionable farming decision-making; and (3) the inclusion of Indigenous People’s in adaptation policy formulation, which might offer context, restore trust, and increase the useability of measures.